The Portrait of Creativity in Using Posters as an Interesting Learning Medium in Grammar Classes: A Narrative Inquiry Study on EFL Teachers - Sujiatmoko, Ahmad Heki; Setyowati, Lestari; MR, Elvira Rasyida (Jurnal Ilmiah Global Education, 2024)
Teacher creativity supported by the use of technology can be achieved by making posters as a Grammar learning medium that can provide significant benefits to students’ success in learning English. This study aimed to reveal the teachers’ perceptions and experiences in fostering creativity through making posters as a Grammar learning medium. This research used a qualitative approach with a 'narrative inquiry' design. The subjects of this study consisted of three teachers from an English learning institution in Malang, Indonesia. This study used depth interviews as an instrument. The results of this study showed that the teachers’ activity through making posters as a learning medium for 'Grammar' grew through three elements consisting of flexibility, originality, and curiosity. The use of posters could also increase productivity and foster technological literacy for teachers. Meanwhile, posters were also able to increase students’ Grammar understanding and learning motivation better. In short, posters had a great positive impact in creating an interesting and fun learning environment. Thus, it is expected that teachers have the ability to make posters as a medium for learning English.